XPC and POLH/XPV Genes Mutated in a Genetic Cluster of Xeroderma Pigmentosum Patients in Northeast Brazil - Castro, Ligia Pereira; Batista-Vieira, Danilo; de Souza, Tiago Antonio; Timoteo, Ana Rafaela de Souza; Coutinho, Jessica Dayanna Landivar; Pinheiro de Almeida, Isabel Cristina; Henriques, Sheila Ramos de Miranda; Azevedo, Fabio Medeiros de; Rosa, Reginaldo Cruz Alves; Kannouche, Patricia L; Sarasin, Alain; Menck, Carlos Frederico Martins; et al. (Frontiers in Genetics, 2022)
Xeroderma pigmentosum (XP) is a rare genetic condition in which exposure to sunlight leads to a high tumor incidence due to defective DNA repair machinery. Herein, we investigated seven patients clinically diagnosed with XP living in a small city, Montanhas (Rio Grande do Norte), in the Northeast region of Brazil. We performed high-throughput sequencing and, surprisingly, identified two different mutated genes. Six patients carry a novel homozygote mutation in the POLH/XPV gene, c.672_673insT [p.Leu225Serfs*33], while one patient carries a homozygote mutation in the XPC gene, c.2251-1 G>C. This latter mutation was previously described in Southeastern Africa (Comoro Island and Mozambique), Pakistan, and in a high incidence in Brazil. The XP-C patient had the first symptoms before the first year of life with aggressive ophthalmologic tumor progression and a melanoma onset at 7 years of age. The XP-V patients presented a milder phenotype with later onset of the disorder (mean age of 16 years old), and one of the six XP-V patients developed melanoma at 72 y. The photoprotection is minimal among them, mainly for the XP-V patients. The differences in the disease severity between XP-C (more aggressive) and XP-V (milder) patients are obvious and point to the major role of photoprotection in the XPs. We estimate that the incidence of XP patients at Montanhas can be higher, but with no diagnosis, due to poor health assistance. Patients still suffer from the stigmatization of the condition, impairing diagnosis, education for sun protection, and medical care.